Size-controlled, colloidally stable and functional nanoparticles based on the molecular assembly of green tea polyphenols and keratins for cancer therapy. Issue 9 (16th February 2018) - Yi, Zeng; Sun, Zhe; Chen, Guangcan; Zhang, Huaiying; Ma, Xiaomin; Su, Wen; Cui, Xinxing; Li, Xudong
Abstract : Molecular assembly of green tea polyphenols and keratins into size-controlled, colloidally stable and functional nanoparticles for enhanced cancer therapy was achieved. Abstract : While intelligent nanoparticles with therapeutic effects provide a resolving strategy for low drug loading efficacy, poor metabolism and elimination of current nanoparticulate drug delivery systems, precise preparation of colloidally stable but stimuli-responsive nanocarriers with size tunability is still a challenging task. Here, we develop a facile and sustainable method through the use of naturally reproducible green tea polyphenols and hair keratins to prepare biocompatible, colloidally stable, stimuli-responsive nanoparticles with therapeutic effects. The present strategy simply involves covalent interactions of tea catechins and keratins, giving rise to the molecular assembly of size-controlled nanoparticles (30–230 nm) which are long-term colloidally stable at physiological media but are disassembled under pathological conditions, ideally for targeted delivery of anticancer drugs. The cell experiments confirmed that these nanoparticles are bio-safe, have the inherent bioactivity of tea catechins, and that the drug-loaded nanoparticles yield a higher cancer cell inhibition rate than free drugs. In addition, the nanoparticles are found to improve the bioavailability of tea polyphenols, according to animal studies, which further demonstrates that the use of nanoparticles as drug carriers results in enhanced anticancer efficacy with negligible systemic toxicity. Given that large-scale preparation of size-controlled nanoparticles could already be easily achieved, the present study actually provides an innovative nanotechnological approach to make good use of green tea polyphenols with beneficial health effects, potentially for therapeutic and preventive purposes.